Influencia Da Comunicacao, Da Identificacao Organizacional E Da Confianca No Desempenho (Global Journal of Management and Business Research, 2019)
In today's globalized and competitive market, the number of organizations working toward the retention of talented personal, who are committed to the institution, is increasing. That happens because the emotional connection between the employee and the company is a competitive advantage. The object of this work is to develop and validate a study model that seeks to identify the influence of communication, organizational identification and trust over the performance of the organization. The research methodology was quantitative descriptive and field research. Data collection was performed using a cross survey through a questionnaire made for this research, with questions structured in linear scale from 1 to 10 and organized in question groups according to the investigated constructs. The research was performed in a soda industry located in the metropolitan region of Belo Horizonte. Altogether, 310 employees from the administrative section, transport and factory were researched. For the statistical analysis were used the exploratory and confirmatory factor analysis, dimensionality, reliability, validity, methods of structured equations, among others
Keywords: communication trust organizational identification performance